2020
DOI: 10.1186/s12909-020-02087-4
|View full text |Cite
|
Sign up to set email alerts
|

What occupational therapists’ say about their competencies’ enactment, maintenance and development in practice? A two-phase mixed methods study

Abstract: Background: Understanding how professional competencies are actually enacted in clinical practice can help university programs better prepare their graduates. The study aimed to describe 1) the perceived competency level of occupational therapists holding an entry-to-practice master's degree 2) the factors perceived as impacting the enactment of competencies; and 3) the strategies used to maintain and further develop level of competency in the seven practice roles: expert in enabling occupation, communicator, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The decrease in the use of EBP could be explained by several individual and organizational factors. Findings from the current study and those from previous studies [57][58][59][60][61] converge to suggest that practitioners highly value their own personal practice experiences and those of their peers as a primary source of knowledge in making clinical decisions. With time and clinical acumen, practitioners' confidence in their abilities increases, and they appear to rely on their experiences as the only or primary source of evidence, especially when they have had successful past experiences in doing so [62,63].…”
Section: Discussionsupporting
confidence: 69%
“…The decrease in the use of EBP could be explained by several individual and organizational factors. Findings from the current study and those from previous studies [57][58][59][60][61] converge to suggest that practitioners highly value their own personal practice experiences and those of their peers as a primary source of knowledge in making clinical decisions. With time and clinical acumen, practitioners' confidence in their abilities increases, and they appear to rely on their experiences as the only or primary source of evidence, especially when they have had successful past experiences in doing so [62,63].…”
Section: Discussionsupporting
confidence: 69%
“…Condon et al 57 found that PTs relied on their peers' opinions rather than on recommendations from research (and moving through the five EBP steps) in making clinical decisions as did Rochette et al, 58 in their study of OTs who perceived that consulting peers was more effective than engaging, for example, in literature searches (one of the five EBP steps). As a note of caution, it is possible that such exchanges among peers may actually be about the nature of the evidence and/or its usefulness in clinical decision making.…”
Section: Discussionmentioning
confidence: 97%
“…As debates on the merits and challenges of EBP grow, 60‐62 clinicians may be turning to colleagues for discussions on topics such as the various conceptions of evidence, 63‐66 the legitimacy of patient narratives in the decision‐making process, 67 and case examples of when the evidence from gold standard designs such as randomized clinical trials conflict with patient choices and/or do not apply to their unique situation 17 . To address the issue of peer exchanges on matters pertaining to EBP, Rochette et al 58 suggested the use of professional networking to improve broader EBP competencies rather than targeting individual discrete skills. Communities of practice and mentorship by more seasoned professionals may also support professionals in this area once they enter practice 68‐70 …”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, occupational therapists’ change agent practices include mainly communication and collaboration actions. According to Rochette and colleagues (2020) , recent occupational therapist graduates in Québec are very comfortable with enacting communicator and collaborator competencies in the clinical setting. Carrier and Beaudoin (2020) noted that the clinical configuration of the change agent role is more aligned with the usual work of occupational therapists, whereas the social configuration involves different types of knowledge and skills.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although previous empirical studies explored occupational therapists' reasons for advocacy actions (Dhillon et al, 2010) and experiences of advocacy activities (Dhillon et al, 2016), to our knowledge, no empirical study has investigated the clinical practice of occupational therapists to identify their concrete change agent actions. Since acting as change agents is considered uncomfortable for most occupational therapists, whether experienced (Finlayson, 2013;Restall & Ripat, 2008) or novice (Rochette et al, 2020), knowing more about what actually happens in practice is of particular interest. More specifically, results might inform educators and professional stakeholders regarding what the objective of future training efforts should be.…”
mentioning
confidence: 99%